(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Islamic civilization is one of the most important cultural and scientific systems in world history. Central Asia, particularly the territory of Uzbekistan, was one of the major centers of Islamic culture and science in the Middle Ages. Great scholars who emerged from this region contributed not only to religious sciences but also to the development of mathematics, medicine, astronomy, geography, and philosophy. This article analyzes the formation of Islamic civilization in Uzbekistan, its historical stages of development, scientific centers, the heritage of scholars, and its significance in the modern era.